PENGARUH UKURAN PERUSAHAAN, PROFITABILITAS, KINERJA KEUANGAN DAN LEVERAGE TERHADAP PENGUNGKAPAN EMISI KARBON (STUDI PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018 - 2020) - Sa'da, Anis Naila (Jurnal KIAFE, 2021)
AbstractThe purpose of this study was to examine the effect of firm size, profitability, financial performance and leverage on the disclosure of carbon emissions. The research method used is quantitative with secondary data types. The population in this study is the energy sector companies listed on the Indonesia Stock Exchange for the period 2018 "“ 2020. The sample collection uses a purposive sampling method and a sample of 18 companies is obtained, so that the number of research samples is 54. To analyze the data using classical assumptions, while testing the hypothesis, regression analysis is used.. The results of this study indicate that profitability has an effect on the disclosure of carbon emissions. Because companies with high profitability are considered to be able to act on environmental pressures that are well received by the company. Meanwhile, Company Size, Financial Performance, and Leverage have no effect on the disclosure of carbon emissions. DAFTAR PUSTAKAAkhiroh, T., & Kiswanto. (2016). The Determinant Of Carbon Emission Disclosures. Accounting Analysis Journal, 5(4), 326"“336.Alvarez, I. G.-, Segura, L., & MartÃnez-Ferrero, J. (2015). Carbon Emission Reduction"¯: The Impact On The Fi Nancial And Operational Performance Of International Companies. 103.Andrew, J., & Cortese, C. (2011). Carbon Disclosures: Comparability, The Carbon Disclosure Project And The Gr...: Ebscohost. Australasian Accounting Business And Finance Journal, 5(4), 5"“18.Andriani, M. (N.D.). Pengaruh Kinerja Keuangan Terhadap Pengungkapan Akuntansi Karbon (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2015).Arikunto, Suharsimi. 2010. Prosedur Penelitian Suatu Pendekatan Praktek. Jakarta: Rineka CiptaBae Choi, B., Lee, D., & Psaros, J. (2013). An Analysis Of Australian Company Carbon Emission Disclosures. Pacific Accounting Review, 25(1), 58"“79.Bahri, Syamsul., Dan Zamzam, Fakhri. (2015). Model Penelitian Kuantitatif Berbasis Sem-Amos. Yogyakarta: Deepublish.Berthelot, S., & Robert, A.-M. (2011). Climate Change Disclosures: An Examination Of Canadian Oil And Gas Firms. Issues In Social And Environmental Accounting, 5(2), 106.Borghei-Ghomi, Z., & Leung, P. (2013). An Empirical Analysis Of The Determinants Of Greenhouse Gas Voluntary Disclosure In Australia. Accounting And Finance Research, 2(1), 110"“127.Cholida, & Kawedar, W. (2020). Analisis Pengaruh Kinerja Keuangan, Kinerja Operasional, Biaya Ekuitas Dalam Pengungkapan Emisi Karbon Untuk Menciptakan Nilai Perusahaan. Diponegoro Journal Of Accounting, 9(2), 1"“11.Cotter, J., & Najah, M. M. (2012). Institutional Investor Influence On Global Climate Change Disclosure Practices. Australian Journal Of Management, 37(2), 169"“187.Fatoni Dkk. 2016. Pengaruh Kepemilikan Publik, Return On Equity, Current Ratio, Umur Perusahaan, Dan Company Size Terhadap Pengungkapan Corporate Social Responsibility. Journal Of Accounting. Vol. 2 No. 2Foundation, E. (2011). Introduction To Village Aquaponics. 324 State Place, Escondido: Ca 92029: Ecolife.Griffiths, A., Haigh, N., & Rassias, J. (2007). A Framework For Understanding Institutional Governance Systems And Climate Change:. The Case Of Australia. European Management Journal, 25(6), 415"“427.Hery. 2015. Analisis Laporan Keuangan. Yogyakarta: Caps (Center For Academic Publishing Service).Iatridis, G. E. (2013). Environmental Disclosure Quality: Evidence On Environmental Performance, Corporate Governance And Value Relevance. Emerging Markets Review, 14(1), 55"“75.Indriantoro,Nur Dan Bambang Supomo. 2011, "Metodologi Penelitian Bisnis Untuk Akuntansi Dan Manajemen", Edisi Pertama. Bpfe,YogyakartaJannah, R., & Muid, D. (2014). Analisis Faktor-Faktor Yang Mempengaruhi Carbon Emission Disclosure Pada Perusahaan Di Indonesia (Studi Empiris Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012). Diponegoro Journal Of Accounting, 3(2), 1000"“1010.Lan, Y., Wang, L., & Zhang, X. (2013). Determinants And Features Of Voluntary Disclosure In The Chinese Stock Market. China Journal Of Accounting Research, 6(4), 265"“285.Lindawati, A. S. L., & Puspita, M. E. (2015). Corporate Social Responsibility: Implikasi Stakeholder Dan Legitimacy Gap Dalam Peningkatan Kinerja Perusahaan. Jurnal Akuntansi Multiparadigma, 157"“174.Luo, L., Tang, Q., & Yi-Cheni, L. (2013). Comparison Of Propensity For Carbon Disclosure Between Developing And Developed Countries. Accounting Research Journal, 26(1), 6"“34.Novianti, W., & Hakim, R. P. (2019). Harga Saham Yang Dipengaruhi Oleh Profitabilitas Dan Struktur Aktiva Dalam Sektor Telekomunikasi. Jurnal Ilmu Keuangan Dan Perbankan (Jika), 7(2), 19"“32.Peraturan Presiden No.61 Pasal 4, 2011. (2011). Peraturan Presiden Republik Indonesia No. 61 Tahun 2012 Tenang Rencana Aksi Nasional Penurunan Emisi Gas Rumah Kaca. Sekretariat Negara"¯: Jakarta, 1"“60.Rokhmawati, A., Gunardi, A., & Rossi, M. (2017). How Powerful Is Your Customers"™ Reaction To Carbon Performance? Linking Carbon And Firm Financial Performance. International Journal Of Energy Economics And Policy, 7(6), 85"“95.Sugiyono. (2017). Metode Penelitian Kuantitatif, Kualitatif, Dan R&D. Bandung : Alfabeta, Cv.Suhardi, Priyambada Robby. (2015). Analisis Faktor "“ Faktor Yang Mempengaruhi Pengungkapan Emisi Karbon Di Indonesia(Studi Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010 -2013). Diponegoro Journal Of Accounting, 4(2), 836"“848.Uyar, A., Kilic, M., & Bayyurt, N. (2013). Association Between Firm Characteristics And Corporate Voluntary Disclosure: Evidence From Turkish Listed Companies. Intangible Capital, 9(4), 1080"“1112.Windi Novianti, W., & Wendy May Agustian, W. (2019). Improving Corporate Values Through The Size Of Companies And Capital Structures. 225 (Icobest), 255"“257.Wiranto, A., & Muaziz, F. (2020). Profitabilitas, Ukuran Perusahaan, Dan Leverage Mempengaruhi Pengungkapan Emisi Karbon Di Indonesia. Jurnal Ekonomi, Bisnis, Dan Akuntansi, 22(1), 28"“41.Yu, H. C., Kuo, L., & Ma, B. (2020). The Drivers Of Carbon Disclosure: Evidence From China"™s Sustainability Plans. Carbon Management, 11(4), 399"“414.Zulaikha, A. P. (2016). Analisis Pengungkapan Emisi Gas Rumah Kaca Anistia Prafitri Zulaikha Departemen Akuntansi Fakultas Ekonomika Dan Bisnis Universitas Diponegoro. 13(2), 155"“175.